Cultural factors influencing dietary and fluid restriction behaviour: perceptions of older Chinese patients with heart failure. Issue 5 (5th December 2016) - Rong, Xiaoshan; Peng, Youqing; Yu, Hai‐Ping; Li, Dan
Abstract : Aims and objectives: To explore the cultural factors related to dietary and fluid restriction behaviours among older Chinese patients. Background: Excess dietary sodium and fluid intake are risk factors contributing to the worsening and rehospitalisation for heart failure in older patients. Managing the complex fluid and diet requirements of heart failure patients is challenging and is made more complicated by cultural variations in self‐management behaviours in response to a health threat. Design: Qualitative study using semi‐structured in interviews and framework analysis. Methods: The design of this study is qualitative descriptive. Semi‐structured in‐depth interviews were conducted with 15 heart failure patients. Data were analysed through content analysis. Results: Seven cultural themes emerged from the qualitative data: the values placed on health and illness, customary way of life, preference for folk care and the Chinese healthcare system, and factors related to kinship and social ties, religion, economics and education. Conclusions: Dietary change and management in response to illness, including heart failure, is closely related to individuals' cultural background. Healthcare providers should have a good understanding of cultural aspects that can influence patients' conformity to medical recommendations. Relevance to clinical practice: Heart failure patients need support that considers their cultural needs. Healthcare providers must have a good understanding of the experiences of people from diverse cultural backgrounds.